A closer look at non-Hodgkin's lymphoma cases in a national Swedish systemic lupus erythematosus cohort: a nested case-control study. Issue 12 (21st May 2007) - Löfström, B; Backlin, C; Sundström, C; Ekbom, A; Lundberg, I E
Abstract : Objective: To investigate risk factors for non-Hodgkin's lymphoma (NHL) and analyse NHL subtypes and characteristics in patients with systemic lupus erythematosus (SLE). Methods: A national SLE cohort identified through SLE discharge diagnoses in the Swedish hospital discharge register during 1964 to 1995 (n = 6438) was linked to the national cancer register. A nested case control study on SLE patients who developed NHL during this observation period was performed with SLE patients without malignancy as controls. Medical records from cases and controls were reviewed. Tissue specimens on which the lymphoma diagnosis was based were retrieved and reclassified according to the WHO classification. NHLs of the subtype diffuse large B cell lymphoma (DLBCL) were subject to additional immunohistochemical staining using antibodies against bcl-6, CD10 and IRF-4 for further subclassification into germinal centre (GC) or non-GC subtypes. Results: 16 patients with SLE had NHL, and the DLBCL subtype dominated (10 cases). The 5-year overall survival and mean age at NHL diagnosis were comparable with NHL in the general population—50% and 61 years, respectively. Cyclophosphamide or azathioprine use did not elevate lymphoma risk, but the risk was elevated if haematological or sicca symptoms, or pulmonary involvement was present in the SLE disease. Two patients had DLBCL-GC subtype and an excellent prognosis. Conclusions: NHL in this national SLE cohort was predominated by the aggressive DLBCL subtype. The prognosis of NHL was comparable with that of the general lymphoma population. There were no indications of treatment-induced lymphomas. Molecular subtyping could be a helpful tool to predict prognosis also in SLE patients with DLBCL.